HUBUNGAN KONDISI KESEHATAN LINGKUNGAN RUMAH BULAT SUKU DAWAN DAN TRADISI SE’I DENGAN KEJADIAN ISPA PADA BAYI DI PUSKESMAS KUANFATU KECAMATAN KUANFATU - Nina Rosenovianty Christiana; Budiyono Budiyono; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
NTT is the province with the highest rates of Acute Respiratory Infection(ARI) in Indonesia 48,03%. One of the top ten disease date in Puskesmas Kuanfatu is ARI with the numbered of infants who experienced ARI 1742 cases. As many as 7,5% of the Kuanfatu people still live in round houses and still practice Se’i tradition. Se’i practice pose a risk the ARI on infant in South Central Timor District. The study aimed to analyze the association between environmental health conditions of the round house and Se’i practice and ARI of the infants in Kuanfatu. This research was an analytic observational research with Cross Sectional design. The sample size who was 48 infants. Statistical analysis used Chi-Square test with 95%Cl and α=5%. The result showed that the incidence of ARI on infant was 64,6%, the numbered of mothers had practice the Se’i 39%, variable did not meet the requirements were occupancy density 44%, temperature28%, dust level 25%. There were significant association between temperature (p=0,036, RP=1,74), dust level (p=0,009, RP=1,93), practice of Se’i (p=0,010, RP=3,34), and length time of Se’i practice (p=0,001, RP=2,50) with incidence of ARI on infants. There were no significant association between density of residence (p=0,237, RP=2,72), air humidity (p=0,597, RP=1,21) and the volume of space house (p=0,860, RP=0,90) with incidence of ARI on infants. The study concluded the round houses (Ume kbubu) had a risk of ARI on infants in terms of air temperature and dust level, the length of time and amount of wood fuel had a risk of ARI on infant.